2024
DOI: 10.1021/acs.jced.3c00564
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Thermodynamic Modeling of Oxaprozin Solubility in Polymers and Mixed Solutions

Haomin Wu,
YingYing Jiang,
Chen Shen
et al.

Abstract: Measuring and modeling the solubility of drugs in different solvent systems is helpful to guide the selection of appropriate solvents at various stages of drug formulation development. In this work, the gravimetrical method was used to determine the solubility data of oxaprozin (OXA) in different compositions of water/organic solvents (methanol and ethanol) binary mixtures within the range of 293.15 to 333.15 K. Subsequently, the differential scanning calorimetry method was used to measure the solubility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The solubility data of the drug in 13 pure organic solvents (methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, isopropanol, methyl acetate, ethyl acetate, 1-propyl acetate, 1-butyl acetate, 1-pentyl acetate, acetonitrile, and acetone) at temperatures ranging from 293.15 to 333.15 K at atmospheric pressure were measured by the gravimetric method. Our previous work has demonstrated the accuracy of this measurement method . The error bars were so small that they were almost invisible in the graph.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…The solubility data of the drug in 13 pure organic solvents (methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, isopropanol, methyl acetate, ethyl acetate, 1-propyl acetate, 1-butyl acetate, 1-pentyl acetate, acetonitrile, and acetone) at temperatures ranging from 293.15 to 333.15 K at atmospheric pressure were measured by the gravimetric method. Our previous work has demonstrated the accuracy of this measurement method . The error bars were so small that they were almost invisible in the graph.…”
Section: Resultsmentioning
confidence: 75%
“…This suggested that PC-SAFT had a good prediction of drug solubility in pure solvents. In addition, Wu et al determined the solubilities of oxaprozin in pure solvents and mixed solvents and predicted these phase equilibrium data by the PC-SAFT combining with solid–liquid equilibrium theory . However, oxaprozin has a hydrogen bond donor while bifendate has no hydrogen bond donors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations